Analysis of the Potential of DynaFlexPro as a Modeling Software by its Application in the Roll Stability of Heavy-Duty Elliptical Tankers using Trammel Pendulum to Simulate Fluid Sloshing - Goru, Venu Gopal (Trinity College Dublin. School of Engineering. Mechanical & Manufacturing Engineering, INSA Lyon, 2007)
One of the most common ways for commercial vehicles to loose their stability is by rollover. Partially filled heavy-duty tankers manoeuvring constant radius turns or lane change maneuvers have lower rollover threshold than other vehicles because of the high center of gravity and dynamic sloshing of the liquid payload. A number of analytical and numerical methods have been used till date to study the motion of fluid in a container and its effect on the container. One of the simplest and most effective ways is by modeling the fluid as a pendulum. Depending on the shape and size of the container, different types of pendulums have been proposed. In this case as the study was based on elliptical cisterns, a trammel pendulum was chosen and the fundamental basis of selecting the appropriate pendulum parameters has been obtained by studies performed by Salem [12]. One of the main aspects of this project is the utilization of completely new multibody computer-aided engineering (MCAE) software packages called DynaFlexPro (DFP) and DynaFlexPro/Tire released in 2005 by MotionPro, Inc and marketed by MapleSoft Inc. These new commercial packages of Maple were chosen to model the Trammel pendulum and the Tractor and articulated Tanker vehicle. Firstly a model of a trammel pendulum was created and it?s kinematic and dynamic effects were studied. The fundamental basis of selecting the appropriate pendulum parameters have been obtained by matching the pendulum dynamic effects with fluid sloshing dynamic effects obtained by using Finite Element (FE) fluid models in the work of Salem. Once a working model was achieved, a 2-D Tanker model was made and the Trammel pendulum model was integrated to study the effect of sloshing on the roll stability of heavy duty tankers. The rollover threshold of 2-D models ranged from 0.9g to 0.25g because of which more realistic 3-D models of Tractor and Tanker were made. Due to some problems in the assembly of Tractor and Tanker, the 3-D Tanker was modified and basic tests were simulated. The 3-D Tanker model predicted critical fill levels that agree with the values reported in the literature based on much more complex and time consuming experimental and analytical methods proving the efficiency of the modeling software. In addition sloshing effects were clearly visible from the results validating the trammel pendulum as a simple and efficient way of modeling sloshing of fluids in elliptical tankers.
Keywords: roll stability; dynaflexpro; articulated vehicles; elliptical tankers